PROFESIONALITAS APOTEKER SEBAGAI PELAKU USAHA DI TINJAU DARI HUKUM PERLINDUNGAN KONSUMEN DI SAMARINDA - Irfan Jaya Kangsaputra (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTIrfan jaya kangsaputra, NPM: 13.11.1001.1011.026, "Professional Pharmacists as Business Actors Reviewed From Consumer Protection Law in Samarinda". (Supervised by Dr.H.Abdul Rokhim, S.H, M.Hum and Drawan Hasyim, S.H, M.Sc).This research was made with the aim to determine the role of pharmacists as health workers does not conflict with pharmacists as entrepreneurs, but this role can lead to conflicts of interest. One effort that can be applied to prevent conflicts of interest is the pharmacist as a professional who works according to his professional code of ethics and has clear and strict provisions as a limitation of duties and functions in owning and / or managing a pharmacy. Thus the government regulations governing the separation of pharmacists in carrying out the duties and functions of managing and / or owning a pharmacy need to be firmly rearranged.The results showed that the profession is an important factor in improving the quality and quantity of work. With the knowledge possessed through education, a person will be able to allocate his thoughts well and tend not to be excessive so that they can work well. Pharmacists as business operators are regulated in Government Regulation No. 25 of 1980 concerning Pharmacy, the government considered that as pharmacists professional pharmacists considered feasible and able to conduct a pharmacy business. Keywords  : Pharmacist, Consumer